Child's play : myth, mimesis and make-believe - Goldman, Laurence (Oxford ; New York : Berg, 1998)
Naming and gaming. Pretend play. Changing roles. The Orge: a melanesian cyclop. The trickster: a melanesian enantiomorph.
Keywords: Child psychology; Play; Magination in children; Child psychology; Play; Symbolic play; Imagination in children; Imitation in children